Implikasi Hukum Perjanjian Damai Amerika Serikat Dan Taliban - Novi D Permatasari; Popi Tuhulele; Wilshen Leatemia (Faculty of Law Universitas Pattimura, 2023)
International agreements in relation to the settlement of international disputes that occur in a country is the basis or benchmark in resolving conflicts that occur in a country. Purposes of the Research provide academic input for the development of legal science, especially in the field of International Law, International Treaty Law related to the regulation and legal impact of the peace treaty between the United States and the Taliban on the stability of Afghan state security. The research method used in this research is normative legal research by reviewing legal literature materials through a statutory approach, case approach and conceptual approach. The sources of legal materials used are primary, secondary and tertiary legal materials. The technique of collecting legal materials is carried out by library research using qualitative analysis techniques. The results of the study show that the agreement between the disputing parties is a formal commitment between the opposing parties to end the war, as stipulated in article 33 paragraph (1) of the UN Charter and in article 2 paragraph (1) of the 1969 Vienna Convention on International Agreements. The implication of the peace agreement between the United States and the Taliban is that there will be political and security instability in Afghanistan which has the potential to last for a long time. Where the Taliban have not created a conducive government system and have not received the support of the international community so it still takes time to create stability for the country of Afghanistan.